Solving the Orienteering Problem with Time Windows via the Pulse Framework. (February 2015) - Duque, Daniel; Lozano, Leonardo; Medaglia, Andrés L.
Abstract: The Orienteering Problem with Time Windows (OPTW) is the problem of finding a path that maximizes the profit available at the nodes in a time-constrained network. The OPTW has multiple applications in transportation, telecommunications, and scheduling. First, we extend an exact method for shortest path problems with side constraints into a general-purpose framework for hard shortest path variants. Then, using this framework, we develop a new method for the OPTW that incorporates problem-specific knowledge. Our method outperforms the state-of-the-art algorithm on instances derived from benchmark datasets from the literature achieving speedups of up to 266 times and is able to find optimal solutions to large-scale problems with up to 562 nodes in short computational times.